2017
DOI: 10.1111/cdev.12847
|View full text |Cite
|
Sign up to set email alerts
|

Waiting for the Second Treat: Developing Culture‐Specific Modes of Self‐Regulation

Abstract: The development of self-regulation has been studied primarily in Western middle-class contexts and has, therefore, neglected what is known about culturally varying self-concepts and socialization strategies. The research reported here compared the self-regulatory competencies of German middle-class (N = 125) and rural Cameroonian Nso preschoolers (N = 76) using the Marshmallow test (Mischel, 2014). Study 1 revealed that 4-year-old Nso children showed better delay-of-gratification performance than their German … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
76
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 41 publications
6
76
1
4
Order By: Relevance
“…Supporting this hypothesis, results of sustained attention and delay-of-gratification assessments suggest that children in Africa, unlike with other abstract cognitive tests, perform at or above Western norms (Lamm, Keller, Teiser, Gudi, Yovsi, Freitag, & Vöhringer, 2018). Supporting this hypothesis, results of sustained attention and delay-of-gratification assessments suggest that children in Africa, unlike with other abstract cognitive tests, perform at or above Western norms (Lamm, Keller, Teiser, Gudi, Yovsi, Freitag, & Vöhringer, 2018).…”
Section: Executive Function and Social-emotional Development In Devmentioning
confidence: 76%
See 1 more Smart Citation
“…Supporting this hypothesis, results of sustained attention and delay-of-gratification assessments suggest that children in Africa, unlike with other abstract cognitive tests, perform at or above Western norms (Lamm, Keller, Teiser, Gudi, Yovsi, Freitag, & Vöhringer, 2018). Supporting this hypothesis, results of sustained attention and delay-of-gratification assessments suggest that children in Africa, unlike with other abstract cognitive tests, perform at or above Western norms (Lamm, Keller, Teiser, Gudi, Yovsi, Freitag, & Vöhringer, 2018).…”
Section: Executive Function and Social-emotional Development In Devmentioning
confidence: 76%
“…Indeed, more studies are highlighting the importance of examining multiple school readiness domains simultaneously rather than separately (e.g., Pace, Burchinal, Alper, Hirsh-Pasek, & Golinkoff, 2018). Furthermore, understanding how non-academic and academic skills unfold over time in cultures that focus on integrating children in to hierarchical social networks (e.g., Lamm et al, 2018), as in the case in Ghana, contribute to a cross-cultural research program that is critical for understanding child development from a global perspective. As close to 90% of children in the world live in a low-or middle-income country (World Bank, 2016), and these children are attending preschool at growing rates (Behrman, Fernald, & Engle, 2013;McCoy, Salhi, Yoshikawa, Black, Britto, & Fink, 2018), research examining children's transition to schooling in developing countries is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the evidence suggests that self‐regulation develops from family support but also from participation in specific types of teaching‐and‐learning communicative interactions within formal education. More interestingly, new studies are starting to show that some types of directive parental communications previously considered to be detrimental for self‐regulation within Western cultures may actually have a null effect on young children's self‐regulation in some Asian countries (Lee, Baker, & Whitebread, ) or even a positive effect in some African cultures (Lamm et al., ). In this study, we explore if what could be conceptualized as the culturally adaptive functionality of self‐regulation development (Torres, ) is also applicable to teacher–student social interactions in classrooms with older children in a Latin American context.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lee, Baker, and Whitebread () have reported that parental intrusiveness or directive talk, which has a negative effect with Western cultures, had no effect on South Korean children's self‐regulation, and Lamm et al. () have reported positive effects in some African cultures. Teacher regulatory talk was conceptualized by Torres et al.…”
mentioning
confidence: 99%